Intraoperative Ultrasound Provides Dynamic, Real-Time Evaluation of the Spinal Cord and Can Be Useful in Cases of Intraoperative Neuromonitoring Signal Changes: A Report of 3 Cases. Issue 1 (January 2020) - Cao, Lisa A.; Skaggs, David L.; Gipsman, Aaron; Kiehna, Erin; Andras, Lindsay M.
Abstract : Cases: We describe 3 pediatric spinal deformity cases that experienced neuromonitoring changes or neurologic changes in which intraoperative ultrasound allowed for evaluation of the site of cord compression to direct management. This resulted in complete neurologic recovery in all 3 patients. Conclusions: Intraoperative ultrasound is a useful adjunct in pediatric orthopaedic spine surgery with neuromonitoring signal loss.